Accessing complex genomic variation in Plasmodium falciparum natural infections - Wendler, J (2015)
Genetic polymorphism in Plasmodium falciparum is a considerable obstacle to malaria intervention. Parasites have repeatedly evolved to overcome every front-line antimalarial deployed throughout history, and artemisinin resistant populations are expanding in Southeast Asia. Promising vaccine candidates routinely fail when challenged by the genetic diversity of natural parasite populations, and a recent trial using a blood-stage antigen showed immunity was allele specific. Modern sequencing technologies have revolutionized our understanding of parasite genomics and population genetics by providing access to single nucleotide variation, but characterizing more complex polymorphism remains a key challenge. Solving this problem is important because the selective pressures from drugs and host immunity often create complex polymorphism in the most clinically relevant genes that is missed using standard genotyping methods. In three sections, this thesis is a narrative about 1) encountering complex variation, 2) overcoming it with novel tools, and then 3) innovatively applying those tools to old and new questions. I first show examples of complex variation in a vaccine candidate (EBA-175) and a drug resistance gene (pfcrt) while reporting SNP based analyses of Kenyan and Tanzanian field isolates. While introducing this complex variation I also describe biological insights discovered in these populations. In Kenya I show evidence that chloroquine resistance selects for parasites that are primaquine sensitive, use a GWAS approach to discover new drug resistance loci, and catalogue variation in known resistance genes. In Tanzania I describe the population structure and allele frequencies of parasites from two geographic regions. In the second section of the thesis I develop methods for accessing complex variation and demonstrate their utility by producing de novo assemblies of eba-175, pfcrt, ama1, and msp3.4 from thousands of sequenced samples. Finally, in the third section I apply these tools in depth to eba-175. I comprehensively characterize the SNP and structural variation in eba-175 using an alignment of 1419 de novo assemblies. I use this resource to illustrate the profiles of positive selection across the gene, and corroborate these signals of balancing selection by showing the geographic distribution of the F/C indels and a lesser known 6bp indel positioned between the DBL domains. I then use the alignments to design Sequenom genotyping assays that facilitate a genome wide association study, testing for human associations with the eba-175 indels in the infecting parasite. I close by reporting a potential association on human chromosome 14 with the 6bp indel in eba-175.